Study of an adaptive bump control mechanism for shock wave/boundary layer interactions in supersonic flows - Shan-Shan Tian; Liang Jin; Wei Huang; Yang Shen; Kai An (Theoretical and Applied Mechanics Letters)
The stability of supersonic inlets faces challenges due to various changes in flight conditions, and flow control methods that address shock wave/boundary layer interactions under only one set of conditions cannot meet developmental requirements. This paper proposes an adaptive bump control scheme and employs dynamic mesh technology for numerical simulation to investigate the unsteady control effects of adaptive bumps. The obtained results indicate that the use of moving bumps to control shock wave/boundary layer interactions is feasible. The adaptive control effects of five different bump speeds are evaluated. Within the range of bump speeds studied, the analysis of the flow field structure reveals the patterns of change in the separation zone area during the control process, as well as the relationship between the bump motion speed and the control effect on the separation zone. It is concluded that the moving bump endows the boundary layer with additional energy.